A field experiment: Testing the potential of norms for achieving behavior change in English parishes. Issue 6 (10th April 2017) - Van de Vyver, Julie; John, Peter
Abstract: Tests of behavioral insights have become increasingly more common, and have been deployed by UK government and agencies. Typically, these field experiments aim to change individual‐level behaviors. The current article tests the potential of behavioral insights for changing group‐level behavior. This article reports the results of a field experiment carried out with the Department of Communities and Local Government. The field experiment tested whether a normative message (vs. a neutral or no message) could encourage parish councils to register an asset of community value (social action). There was no statistically significant effect from this intervention, but the process of designing and implementing this field experiment shows the potential for theories of behavior change to be used by government departments.